"Further education, future prosperity? The Implications of Marketisation on Further Education Working Practices". Issue 4 (2nd October 2017) - Illsley, Rachael; Waller, Richard
Abstract: This paper examines how the marketised funding system of vocational further education is affecting lecturers' working practices and professional integrity. Semi-structured interviews were conducted with a number of lecturing staff and managers within two vocational areas at an English FE college to examine the implications of working under the current funding regime. The conclusions drawn reflect the complexity of working within FE showing how lecturers are frequently placed in a professional dilemma between securing future funding (by ensuring high levels of retention and achievement) and compromising their professional integrity and working practices in order to do so. A key finding here was the inherent tension between professional integrity and funding requirements apparently directly opposing 'good' practice. This means FE professionals experience what Whitehead called 'a living contradiction' in their working lives, increasing stress levels and diminishing their sense of professionalism.